2018
DOI: 10.1038/s41598-018-29659-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases neutrophil-driven matrix destruction after exposure to Mycobacterium tuberculosis

Abstract: The importance of neutrophils in the pathology of tuberculosis (TB) has been recently established. We demonstrated that TB lesions in man are hypoxic, but how neutrophils in hypoxia influence lung tissue damage is unknown. We investigated the effect of hypoxia on neutrophil-derived enzymes and tissue destruction in TB. Human neutrophils were stimulated with M. tuberculosis (M.tb) or conditioned media from M.tb-infected monocytes (CoMTB). Neutrophil matrix metalloproteinase-8/-9 and elastase secretion were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 39 publications
(45 reference statements)
3
55
2
Order By: Relevance
“…Neutrophils isolated from healthy volunteers subjected to acute hypoxia showed increased neutrophil elastase (NE) release ex vivo [23], although these cells experienced ambient oxygen during isolation and on subsequent culture ("hypoxia-re-oxygenation"). Consistent with these results; however, isolated human neutrophils incubated under hypoxia released more NE, MPO, lactoferrin, MMP-8, and MMP-9 when compared with normoxia, representing increased secretion of azurophil, specific and gelatinase granules [24,25]. McGovern et al and Hoenderdos et al found that this hypoxia-augmented degranulation occurred rapidly (within 2 h), was not prevented by inhibition of protein translation, and could not be recapitulated by pharmacological HIF-1α stabilisation [24,32].…”
Section: Hypoxia Enhances Neutrophil Degranulationsupporting
confidence: 67%
See 4 more Smart Citations
“…Neutrophils isolated from healthy volunteers subjected to acute hypoxia showed increased neutrophil elastase (NE) release ex vivo [23], although these cells experienced ambient oxygen during isolation and on subsequent culture ("hypoxia-re-oxygenation"). Consistent with these results; however, isolated human neutrophils incubated under hypoxia released more NE, MPO, lactoferrin, MMP-8, and MMP-9 when compared with normoxia, representing increased secretion of azurophil, specific and gelatinase granules [24,25]. McGovern et al and Hoenderdos et al found that this hypoxia-augmented degranulation occurred rapidly (within 2 h), was not prevented by inhibition of protein translation, and could not be recapitulated by pharmacological HIF-1α stabilisation [24,32].…”
Section: Hypoxia Enhances Neutrophil Degranulationsupporting
confidence: 67%
“…It should be noted that the degree of neutrophil apoptosis under normoxia versus hypoxia begins to diverge after 5 h in culture, with significantly improved cell survival under hypoxia beyond 20 h, which may contribute to observed changes in protein secretion at later time points [95]. However, in this study, the authors demonstrated no significant difference in cell viability between normoxic versus hypoxic neutrophils exposed to media from tuberculosis (TB)-infected monocytes, as stimulated cells exhibited prolonged survival, which was not further augmented by hypoxia [25]. Consistent with this work, three further studies have suggested HIF-dependent changes in mRNA or protein content of selected neutrophil granule proteins (Figure 1).…”
Section: Role Of Hif In Neutrophil Degranulation Under Hypoxiamentioning
confidence: 54%
See 3 more Smart Citations